2016
DOI: 10.1111/mcn.12250
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of locally produced ready‐to‐use therapeutic foods in Ethiopia, Ghana, Pakistan and India

Abstract: Successful treatment of severe acute malnutrition has been achieved with ready-to-use therapeutic food (RUTF), but only 15% of children with severe acute malnutrition receive RUTF. The objective of this study was to determine whether new formulations of RUTF produced using locally available ingredients were acceptable to young children in Ethiopia, Ghana, Pakistan and India. The local RUTFs were formulated using a linear programming tool that allows for inclusion of only local ingredients and minimizes cost. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 13 publications
2
40
2
Order By: Relevance
“…However, our consumer test results are only preliminary, because only healthy adults are included. Indeed, it is well known that children/adults with SAM would also be more willing to consume RUTF than well‐nourished children/adults (Weber et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our consumer test results are only preliminary, because only healthy adults are included. Indeed, it is well known that children/adults with SAM would also be more willing to consume RUTF than well‐nourished children/adults (Weber et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In some recent reviews (Brixi, 2018; Weber et al., 2017) and papers (Owino, Irena, Dibari, & Collins, 2014), it was reported that several RUTF formulations were proposed in several countries, such as Ethiopia, Ghana, Pakistan, and India, containing different legumes (almond, lentil, and soy), cereals (maize and oat), other oils (canola, rapeseed, coconut, and sunflower), and different forms of whey (acid whey milk and whey protein concentrate). In all the alternative RUTF formulations proposed, the inclusion of a vitamin and mineral premix was necessary, to ensure a balanced micronutrient intake of the final product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All children were managed according to National Integrated Management of Neonatal and Childhood Illnesses (IMNCI) guidelines for SAM and associated infections and other complications like hypothermia and hypoglycemia 11. Immunization status was considered as complete if vaccinated according to WHO schedule 12…”
Section: Methodsmentioning
confidence: 99%
“…There is an acknowledged need for the development of novel RUFs and their comparison with existing products (S. de Pee, Bloem, MW, ; Kuusipalo, Maleta, Briend, Manary, & Ashorn, ; Lazzerini, ; Manary, ; WHO, ). In the past decade, numerous studies have aimed to contribute to an understanding of the use of locally produced specialised foods (Ackatia‐Armah et al, ; Ahmed et al, ; Anderson, Bediako‐Amoa, & Steiner‐Asiedu, Anderson, Bediako‐Amoa, & Steiner‐Asiedu, ; Arimond et al, ; Bauserman et al, ; Bogard et al, ; Flax et al, ; Hy Ta & Martinaud, ; Iuel‐Brockdorf et al, ; Lagrone, Cole, Schondelmeyer, Maleta, & Manary, ; Lagrone et al, ; Skau et al, ; Weber et al, ).…”
Section: Introductionmentioning
confidence: 99%